USE OF NANOTECHNOLOGY IN CANCER TREATMENT: A REVIEW - AHMAD , MT; NOOR , M; HAIDER , MU; SHAUKAT , H; SALEEM , HF; DIN , HMU; NASIR , NA; RAO , MA; KHAN , MNUR; TARIQ , MB (Biological and Clinical Sciences Research Journal, 2024)
Nanotechnology has become a revolutionary instrument in cancer treatment, providing unparalleled possibilities for boosting drug administration, increasing treatment selectivity, and decreasing systemic toxicity. This review aims to analyze the use of nanoparticles in cancer treatment, explicitly emphasizing drug delivery methods, cancer immunotherapy, and the mitigation of multidrug resistance. This paper aims to thoroughly analyze the main developments in nanoparticle-based therapeutics by synthesizing existing research. Additionally, it will highlight essential deficiencies in the literature, including the restricted clinical use and long-term biocompatibility of these technologies. This study will evaluate research conducted in the last ten years, focusing on recent advancements in nanotechnology, specifically its ability to improve chemotherapy and radiation by leveraging synergistic effects. The investigation will also investigate the obstacles encountered in the field, such as regulatory gaps and safety issues, that hinder the broader implementation of nanotechnology in cancer. Finally, this review will provide valuable perspectives on the future of nanomedicine in cancer therapy, suggesting particular domains for additional studies, such as more rigorous clinical trials and more thorough examinations of nanoparticle interactions within the tumor microenvironment. The results will improve patient outcomes by contributing to the creation of more individualized and efficient cancer treatments.